Mỹ So’n in Green: a painting of the Champa sanctuary of Mỹ So’n by Đàng Năng Tho - Nakamura, Rie (2015)
This article examines a painting of the Mỹ So’n sanctuary of the historical kingdom of Champa by a Cham ethnic minority artist, Đàng Năng Thọ’. The Cham people are thought to be the descendants of the Champa kingdom and are one of 54 state-recognized ethnic groups in Vietnam.Due to their historical conflicts with the Vietnamese and their participation in ethno-nationalistic movements in the 1960s, Cham-related issues are considered to be “sensitive”. Mỹ So’n is a Hindu sanctuary of the Cham royalty constructed between the 4th and 13th centuries. Mỹ So’n is considered the most significant religious site of Champa at its height.In 1999 Mỹ So’n was listed as a World Heritage Site by UNESCO.Mỹ So’n has become one of the Vietnam’s most significant cultural heritages, and Vietnamese artists take Mỹ So’n as their theme for artistic creation. This article is an endeavor to decipher the message that a painting of Mỹ So’n sanctuary by Đàng Năng Thọ’ conveys.His assertion of Mỹ So’n as the Cham people’s spiritual homeland and the possibility of art as a strategy for the ethnic minority people to claim ownership of their cultural heritage are argued.